Cold, cold bones [large type] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2022)
"Freed from a heavy work schedule, Tempe Brennan is content to dote on her daughter Katy, finally returned to civilian life from the army. But when mother and daughter meet at Tempe's place one night, they find a box on the back porch. Inside: a very fresh human eyeball. GPS coordinates etched into the eyeball lead to an equally macabre discovery. Soon after, Tempe examines a corpse and her anxiety deepens. There seems to be no pattern to the subsequent killings, except that each mimics in some way a homicide that a younger Tempe had been called in to analyze. Who or what is targeting her, and why?"--